Value creation in cross-sector collaborations: a value analysis of business and non-profit partnerships in Malaysia - Dwarkasing, Shanta Helena (2018)
Over the past decade, there has been an increase of non-profit organizations and businesses moving into cross-sector collaborations. Some of the cross-sector collaborations have evolved into advanced stages that co-develop entirely new business models.